INTEGRASI LATIHAN VESTIBULAR-POSTURAL (V-POST) DALAM MENINGKATKAN KONTROL MOTORIK: STUDI KASUS PADA ANAK DENGAN GANGGUAN SENSORI DAN PERILAKU DI KLINIK X SURABAYA: Indonesia - Khabib Abdullah; Nura Maulida Isna; Sarah As Syifa (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2026)
Sensory Processing Disorder (SPD) adversely affects motor control, weakens postural muscles, and causes physical instability in children. Cases at Clinic X Surabaya indicate that this physical issue is frequently accompanied by behavioral challenges such as sensory seeking, hyperactivity, and poor focus, as the child feels unsafe against gravity (gravitational insecurity), which triggers a stress response (fight-or-flight). To overcome the limitations of conventional therapy that only strengthens muscles in isolation, this single-subject research with an A-B design evaluates the level 2 hybrid protocol